Data mining of near‐Earth asteroids in the Subaru Suprime‐Cam archive2. Issue 5 (6th June 2017) - Vaduvescu, O.; Conovici, M.; Popescu, M.; Sonka, A.; Paraschiv, A.; Lacatus, D.; Tudorica, A.; Hudin, L.; Curelaru, L.; Inceu, V.; Zavoianu, D.; Cornea, R.; et al.
Abstract : As part of the EURONEAR project, almost 70, 000 mosaic Suprime‐Cam images taken between 1999 and 2013 were data‐mined for about 9, 800 near‐Earth asteroids (NEAs) known by 2013 May. Using our PRECOVERY server and the new Find Subaru CCD tool, we scrutinized 4, 186 candidate CCD images possibly holding 518 NEAs. We found 113 NEAs as faint as V <25 magnitude, their positions being measured in 589 images using Astrometrica, and then reported to the Minor Planet Center. Among them, 18 objects represent encounters of previously single opposition NEAs, their orbital arcs being extended by up to 10 years. In the second part of this work, we searched for unknown NEAs in 78 sequences (780 CCD fields) of 4–5 mosaic images selected from the same Suprime‐Cam archive and totaling 16.6 deg 2, with the aim to assess the faint NEA distribution observable with an 8‐m class survey. A total of 2, 018 moving objects were measured, from which we identified 18 better NEA candidates. Using the R c filter in good weather conditions, mostly dark time and sky directions slightly biased towards the ecliptic, at least one NEA could be discovered in every 1 deg 2 surveyed.